Formulasi Pendidikan Inklusif-Humanis bagi Disabilitas: Perspektif Filosofis John Dewey, Paulo Freire, dan Abuddin Nata - Sugeng Santoso (Pustaka Peradaban, 2023)
Inclusive-humanist education is a pedagogical concept that endeavors to create an educational environment conducive to individuals with disabilities. This form of education aims to develop a system that humanizes disabled learners, enabling them to strive and cultivate their potential independently. To formulate the concept of inclusive-humanist education for individuals with disabilities, the author conducts a comparative analysis of the viewpoints of several influential figures focused on humanistic thought, namely John Dewey, Paulo Freire, and Abuddin Nata. John Dewey, a notable humanist thinker, asserts that learners are deemed autonomous in making decisions, solving problems, and unfolding their potential, devoid of external influences. Conversely, Paulo Freire constructs an educational framework that emerges from exigent circumstances, rooted in the fundamental assumption that the realities experienced by individuals constitute an evolving process, destined to become a stepping stone towards freedom. Abuddin Nata, a distinguished scholar in Islamic education, expounds that education is a means to explore the process of humanizing individuals, wherein each person is endowed with the freedom to determine their life choices, in accordance with the decree of Allah SWT. This decree signifies that a community’s transformation hinges upon the transformation of its constituents.The synthesis of these perspectives highlights the urgency of a humanistic, inclusive approach to education for individuals with disabilities. Pendidikan inklusif-humanis merupakan konsep pendidikan yang berupaya menciptakan lingkungan pendidikan yang ramah bagi bagi difabel. Pendidikan ini juga mengembangkan sistem yang memanusiakan peserta didik difabel, sehingga mereka dapat berjuang dan mengembangkan potensinya dengan kemampuannya sendiri. Untuk memformulasikan pemikiran pendidikan inklusif-humanis bagi difabel, penulis mengkomparasikan pemikiran beberapa tokoh yang berfokus pada pemikiran humanisme, yakni John Dewey, Paulo Freire, dan Abuddin Nata. John Dewey adalah salah satu pemikir humanis dan mengemukakan bahwa peserta didik dianggap memiliki kemandirian dalam mengambil keputusan, memecahkan masalah dan mengembangkan potensinya tanpa dipengaruhi faktor di luar dirinya. Paulo Freire, di sisi lain, membangun sebuah konsep pendidikan yang berangkat dari keadaan yang memaksa dirinya untuk berkembang, dan pada dasarnya manusia menggunakan asumsi dasar bahwa kenyataan yang dialami oleh manusia merupakan sebuah proses, dan nantinya akan menjadi batu pijakan menuju sebuah kebebasan. Sedangkan Abuddin Nata yang merupakan salah satu pakar pendidikan Islam, yang menjelaskan bahwa pendidikan adalah salah satu metode dalam mempelajari proses memanusiakan manusia, dan setiap manusia diberikan kebebasan untuk menentukan pilihan hidupnya, sesuai dengan firman Allah SWT. yang menjelaskan tidak akan mengubah keadaan suatu kaum sebelum mereka mengubah keadaan diri mereka sendiri